Synthesis and Characterization of Novel ssDNA X-Aptamers Targeting Growth Hormone Releasing Hormone (GHRH) - ŞAHİN, BURCU AYHAN; APAYDIN, ZEYNEP-ELİF; Çoker-Gürkan, Ajda; ARISAN, ELİF DAMLA; YERLİKAYA, PINAR OBAKAN (Public Library Science, 2022)
Background Growth Hormone Releasing Hormone (GHRH), 44 amino acids containing hypothalamic hormone, retains the biological activity by its first 29 amino acids. GHRH (NH2 1-29) peptide antagonists inhibit the growth of prostate, breast, ovarian, renal, gastric, pancreatic cancer in vitro and in vivo. Aptamers, single-strand RNA, or DNA oligonucleotides are capable of binding to target molecules with high affinity. Our aim in this study is to synthesize and select X-aptamers against both GHRH NH2 (1-29) and GHRH NH2 (1-44) and demonstrate synthesized aptamers' target binding activity as well as serum stability. Methods and results Aptamers against GHRH NH2 (1-44) and NH2 (1-29) peptides were synthesized, and binding affinity (K-d) of 24 putative X-aptamers was determined by the dot-blot method, co-immunofluorescence staining and, SPR analysis. The serum stability of TKY.T1.08, TKY1.T1.13, TKY.T2.08, TKY.T2.09 X-aptamers was 90-120 h, respectively. The dose-dependent binding of TKY1.T1.13, TKY.T2.08, TKY.T2.09 X-aptamers on GHRHR in MIA PaCa-2 was approved by co-IF assay results. Moreover, SPR analysis indicated the Kd (4.75, 1.21, and 4.0 nM) levels of TKY2.T1.13, TKY.T2.08, TKY.T2.09 putative X-aptamers, respectively. Conclusion Our results illustrate the synthesis of 24 putative X-aptamers against both GHRH NH2 (1-44) and NH2 (1-29) peptides and TKY1.T1.13, TKY.T2.08, TKY.T2.09 X-aptamers have high serum stability, high target binding potential with low K-d levels.
Keywords: In-vitro Selection